The role of stakeholders in the diffusion of innovations within social organisations - Javangwe, Romayne (2019)
The purpose of this study was to explore the role of stakeholders in the diffusion of innovation within social organizations. This research is in response to a rise in social challenges, which are beginning to negatively impact our economies and society as a whole. In order for social organizations to be effective, they need to be able to successfully spread ideas within the organization, while engaging all the relevant stakeholders, who are essential for the implementation of those ideas.